Effect of Antimicrobial Stewardship on Oral Quinolone Use and Resistance Patterns over 8 Years (2013-2020) - Atsushi Uda; Katsumi Shigemura; Koichi Kitagawa; Kayo Osawa; Mari Kusuki; Yonmin Yan; Ikuko Yano; Takayuki Miyara (MDPI AG, 2021)
Since 2014, several global and national guidelines have been introduced to address the problem of antimicrobial resistance. We conducted a campaign in a tertiary hospital to promote appropriate quinolone use through educational lectures in 2018. The aim of this retrospective study was to evaluate the changes in the following: prescription characteristics, trend of oral quinolone use, and antibiotic susceptibility of bacteria from 2013 to 2020. Antimicrobial use was assessed as days of therapy per 1000 patient-days. We found a significant reduction in unnecessary antibiotic prescriptions between December 2013 and December 2020. Significant negative trends were detected in the use of quinolones over 8 years (outpatients, coefficient = −0.15655, p < 0.001; inpatients, coefficient = −0.004825, p = 0.0016). In particular, the monthly mean use of quinolones among outpatients significantly decreased by 11% from 2013 to 2014 (p < 0.05) and reduced further by 31% from 2017 to 2020 (p < 0.001). A significant positive trend was observed in the susceptibility of Pseudomonas aeruginosa to levofloxacin (p < 0.001). These results demonstrate that the use of oral quinolones was further reduced following educational intervention and the bacterial susceptibility improved with optimal quinolone usage compared to that in 2013.